Modification of streoidal compounds by biotransformation as a green synthetic tool / Mohd Zaimi Mohd Noor … [et al.] - Mohd Noor, Mohd Zaimi; Sultan, Sadia; El Hassane, Anouar; Syed Ali Syah, Syed Adnan (Research Innovation Business Unit, 2014)
Bio transformation is considered one of the foundational pillars of green chemistry practice. Chemical modification through bio transformation are performed in mild condition, room temperature, in water-based syntheses pot and can provide efficient alternative to chemical syntheses as the microbial transformation can reduce the use and generation of hazardous substances. Bio transformation is an important tool for compound modification of organic compound, especially natural product with complex structures like steroids. Microorganisms whole cell-based bio transformation have been carried out by using steroidal compounds as the starting point and a range of fungi have been screened in this bio conversion activity. This research is focused on the structural modifications of steroids mediated by fungi, in order to investigate the effect of culture on substrate. This study investigated the effect of Tri chothecium roseum and SSW endophyte and it is carried out for the first time. Bio transformation of tibolone by fungal Tri chothecium roseum yielded five metabolites. The hydro xylations were mainly undergone in rings A, B and C, especially at C-3, C-6 and C-12 positions. The structural modification of an anti- inflammatory drug, prednisolone by marine endophytic fungus coded as SSW isolated from marine algae sea weed was reported for the first time. The bio transformation led to the formation of a known compound named 20 beta- hydroxy prednisolone. Transformation of 21 - acetyl prednisolone was done in parallel with prednisolone in order to see the effect of side chain of prednisolone in bio transformation. Endophytic fungus Penicillium lapidosum (SSW) also gave a positive result on de acetylation of 21 - acetyl prednisolone to prednisolone in two days fermentation and finally transformed to 20 beta- hydroxy prednisolone after six days fermentation. The absolute configuration of 20 beta- hydroxy prednisolone was also confirmed for the first time by both experimental and calculated chemical coupling constants and ECD spectra. Endo phytic fungus SSW was identified as a Penicillium lapidosum by sequencing against Blasting 2.2.10 of the U.S National Centre for Biological Information (NCBI).